Hubungan Kepemimpinan dan Motivasi Kerja Pegawai dengan Kinerja Puskesmas di Kabupaten Jember (The Correlation between Leadership and Employee’s Work Motivation with Working Performance of Public Health Center in Jember) - Reni Chairunnisah; Nuryadi Nuryadi; Eri Witcahyo (Pustaka Kesehatan, 2014)
The working performance of Public Health Center (PHC) is very essential in health development efforts. The working performances of PHC in 2012 is recorded from 89,7 to 144,20 and in 2013 is from 110,02 to 156,14. These values are far below the standard of 199. This shows that there is a problem of low working performance of PHC in Jember. This study aims to analyze the correlation between leadership and employee motivation to the working performance of PHC in Jember. The study is an analytical research with quantitative design. The number of sample was 316 respondent. The data were analyzed by using the Spearman rank correlation test. The result of the study showed that the leadership is in the category of good and very good leadership (89,9%), employees work motivation is in the medium category (63%) and it also showed that the performance of PHC in Jember is in the medium category. The analysis results indicate that there is a correlation between leadership and the working performance of PHC (0,049